2017
DOI: 10.1016/j.ijforecast.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of product involvement and emotion on short-term product demand forecasting

Abstract: a b s t r a c tSales forecasters in industries like fast-fashion face challenges posed by short and highly volatile sales time series. Computers can produce statistical forecasts, but these are often adjusted judgmentally to take into account factors such as market intelligence. We explore the effects of two potential influences on these adjustments: the forecaster's involvement with the product category and their emotional reactions to particular products. Two forecasting experiments were conducted using data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Product involvement affects the evaluation and actual purchase of a product by consumers. Product involvement is an important factor for consumer product choice ( Belvedere and Goodwin, 2017 ). When consumers perceive usefulness and trust through UGC interaction, they are involved in the product, and will consider the uncertain consequences of the product, resulting in perceived risk ( Rahman, 2017 ; Habib et al, 2021 ).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Product involvement affects the evaluation and actual purchase of a product by consumers. Product involvement is an important factor for consumer product choice ( Belvedere and Goodwin, 2017 ). When consumers perceive usefulness and trust through UGC interaction, they are involved in the product, and will consider the uncertain consequences of the product, resulting in perceived risk ( Rahman, 2017 ; Habib et al, 2021 ).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Therefore, we should consider the characteristics of information receivers when analyzing the impact of UGC on consumers. Product involvement in the communication effect has helped explain consumer behavior in advertising, promotion stimulation, information search, and processing ( Zaichkowsky, 1985 ; Belvedere and Goodwin, 2017 ). Therefore, this study introduces consumer product involvement as the moderating variable.…”
Section: Introductionmentioning
confidence: 99%
“…This is further amplified by the judgmental processes used for new products (Kahn & Chase, 2018). We see an interesting avenue of future research in how this new kind of marketing intelligence can integrate into decision‐making processes, hopefully mitigating biases involved with new products (Belvedere & Goodwin, 2017; Markovitch et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research on adjusting forecasts from statistical models found that adjustments often increase errors (e.g. Belvedere & Goodwin, 2017;Fildes & Goodwin, 2007) or have mixed results (e.g. Franses, 2014;Lin, Goodwin, & Song, 2014)" (Armstrong & Green, 2018a, 2018b.…”
Section: Covid-19 Deaths Inmentioning
confidence: 99%